Duración de la instrucción fiscal, referente al código orgánico integral penal. - Morocho Ortíz, Luz Marina (2018)
The present research work whose subject is "DURATION OF THE FISCAL INSTRUCTION, REFERRING TO THE COMPREHENSIVE ORGANIC CODE OF CRIME" The objective of this research work is oriented to the legal and critical analysis of the procedures and claims in the application of the functions of the Office of the Prosecutor , as well as establishing a legal reform to the Comprehensive Criminal Organic Code, for addressing a subject of the Ecuadorian legal and social reality. It is oriented to the legal and critical analysis of the procedures and claims in the application of the functions of the Office of the Prosecutor, as well as to establish a legal reform to the Organic Comprehensive Criminal Code, for addressing a subject of the Ecuadorian juridical and social reality. It is established that the duration of the fiscal instruction is thirty days but it begins after the prosecutor in charge finishes the ninety days or when it deems convenient, this leaves the juridical vulnerability to the defendant. The Fiscal Instruction, which as its name identifies it, is the stage in which the prosecutor exposes before the corresponding Criminal Court, the detailed identification of each of the evidentiary elements that allow the judicial authorities to know about the responsibility of the accused in the commission of the crime. The crimes dealt with in the criminal action are divided into crimes of public action and crimes of private action, being those of public action, those that present an injury not only to their direct victim but to the whole society, such as crimes against property, sexual crimes or crimes against life, among others. In this case, the action of the Office of the Public Prosecutor is part of the crimes of public action, constituting the Office of the Public Prosecutor in the defense of society against the commission of the crimes that injure her or put her at risk, at the request of a party initiate a thorough investigation process, called 'Previous Research', by presenting the corresponding complaint, or ex officio, by knowing the commission of the infraction or the injurious result. It is in this initial phase of the previous investigation, in which the Public Prosecutor's Office collects all the evidentiary elements that will then serve to demonstrate their theory of the case and establish the responsibility of the author, accomplice and accessory to a crime, and once the investigation is completed, request to one of the local Judges, hearing to formulate charges, so that in case of possessing the necessary elements, the Fiscal Instruction will be opened for 90 days. During these ninety days, the Office of the Prosecutor will conclude its investigation by preparing a final report of the Prosecution, which will raise the case that is presented before the competent Criminal Court, before whom the hearing for a trial will be held against the alleged offender, all this, without up to that point any responsibility has been determined against the accused, based on assumptions and evidence that allow him to support his case to the Prosecutor in charge, before the society and the administration of justice of the country. It is important that as professionals and as citizens interested in the development of public and legal life of the State we know these criminal procedures, necessary for the achievement of the so-called "theory of the case" which will allow to establish a process of accusation against whoever is consider violator of the Law.